Fluctuations in agriculture and sediment in the Mekong delta of Vietnam due to increased upstream water use - Bui, Viet Hung; Nguyen, Ngoc Diep (Vietnam Journal of Science, Technology and Engineering, 2021)
The Mekong delta (MD) of Vietnam rests at the end of the lower Mekong basin (LMB) where it is met with serious adverse effects from all upstream activities with severe consequences like landslides and complicated subsidence phenomena. Researchers agree that the main reason for these consequences are the lack of sediment deposited in MD due to the absence of floods and upstream hydropower development. To better understand the causes of the above phenomena, research on the transboundary impact between Vietnam and Cambodia in the MD was carried out [1]. This article develops more reliable scientific evidence of the impacts of upstream water use on the economic, social, and environmental factors of its four national members. It also scientifically demonstrates the transboundary impacts of upstream hydropower and irrigation developments in LMB such as the decline of sediment and the extreme decline of the quantity/yield from natural fisheries under all development scenarios.